2019
DOI: 10.3389/fcell.2019.00127
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Rho GTPase Signaling at the Endomembranes

Abstract: The Rho family of small GTPases orchestrates fundamental biological processes such as cell cycle progression, cell migration, and actin cytoskeleton dynamics, and their aberrant signaling is linked to numerous human diseases and disorders. Traditionally, active Rho GTPase proteins were proposed to reside and function predominantly at the plasma membrane. While this view still holds true, it is emerging that active pool of multiple Rho GTPases are in part localized to endomembranes such as endosomes and the Gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 83 publications
3
80
0
Order By: Relevance
“…The canonical picture states that activated RhoA is restricted at plasma membrane (Garcia-Mata et al, 2011; Hodge and Ridley, 2016). While transmembrane receptor trafficking, such as for integrins or cadherins, has been under intense scrutiny in the context of cell migration and cancer metastasis (Mellman and Yarden, 2013; Paul et al, 2015; Kajiho et al, 2018), the link between traffic and Rho GTPases is only now coming to the fore and our data support the new idea that “endosomes serve as a hub for Rho GTPase activation and spatiotemporal signal generation” (Phuyal and Farhan, 2019). Recent studies highlighted the presence of active Rho GTPases in intracellular membranes and argue for an origin of Rho signaling from the endosomal network (Phuyal and Farhan, 2019).…”
Section: Discussionsupporting
confidence: 66%
“…The canonical picture states that activated RhoA is restricted at plasma membrane (Garcia-Mata et al, 2011; Hodge and Ridley, 2016). While transmembrane receptor trafficking, such as for integrins or cadherins, has been under intense scrutiny in the context of cell migration and cancer metastasis (Mellman and Yarden, 2013; Paul et al, 2015; Kajiho et al, 2018), the link between traffic and Rho GTPases is only now coming to the fore and our data support the new idea that “endosomes serve as a hub for Rho GTPase activation and spatiotemporal signal generation” (Phuyal and Farhan, 2019). Recent studies highlighted the presence of active Rho GTPases in intracellular membranes and argue for an origin of Rho signaling from the endosomal network (Phuyal and Farhan, 2019).…”
Section: Discussionsupporting
confidence: 66%
“…As described above, Rac1 and Cdc42 GTPases transduce TCR signals driving actin cytoskeleton remodeling during immunological synapse formation. These molecules were shown to be associated with vesicles in other cellular types (Phuyal and Farhan, 2019). Interestingly, we observed that a minor fraction of Rac1 in T cells colocalizes with Rab11 + recycling endosomes, whereas most of the Rac1 protein seems to be associated with the plasma membrane or diffused in the cytosol.…”
Section: Vesicle Traffic Controls Tcr Signaling and The Cytoskeletonmentioning
confidence: 66%
“…Such specialized roles may reflect selective activation of different intracellular pools of Rac1, which would depend on Rac-GEFs localized at discrete locations. Crucially, Rac1 can be expressed and activated in a range of intracellular compartments, including the nucleus, endosomes and mitochondria, and a similar scenario has been described for Rac-GEFs (Justilien et al, 2017;Abdrabou and Wang, 2018;Pan et al, 2018;Phuyal and Farhan, 2019). One interesting example is the activation of rRNA synthesis and tumorigenesis in the nucleolus of lung cancer cells by the GEF Ect2, thus implicating Rac1 in ribosomal biogenesis (Justilien et al, 2017), a process associated with tumor growth, EMT and metastasis (Prakash et al, 2019).…”
Section: Location Is the Key: Why Do Cancer Cells Need Multiple Rac-gmentioning
confidence: 74%